2003
DOI: 10.1038/nrm1200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and unclear functions of SUMO

Abstract: Post-translational modification by the ubiquitin-like SUMO protein is emerging as a defining feature of eukaryotic cells. Sumoylation has crucial roles in the regulatory challenges that face nucleate cells, including the control of nucleocytoplasmic signalling and transport and the faithful replication of a large and complex genome, as well as the regulation of gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
600
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(636 citation statements)
references
References 128 publications
23
600
1
12
Order By: Relevance
“…In the present study, we have demonstrated that endogenous PIASy acts as a negative Recent accumulated studies have demonstrated that many proteins involved in cell-cycle regulation, proliferation, apoptosis and DNA repair are targets for sumoylation, and indicated that alterations in sumoylation could ultimately have impacts on cell growth, cancer development and drug responsiveness [9,25]. Therefore, regulation of sumoylation is tightly linked to homeostasis, and dysregulation of sumoylation may play significant roles in pathological disorders.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, we have demonstrated that endogenous PIASy acts as a negative Recent accumulated studies have demonstrated that many proteins involved in cell-cycle regulation, proliferation, apoptosis and DNA repair are targets for sumoylation, and indicated that alterations in sumoylation could ultimately have impacts on cell growth, cancer development and drug responsiveness [9,25]. Therefore, regulation of sumoylation is tightly linked to homeostasis, and dysregulation of sumoylation may play significant roles in pathological disorders.…”
Section: Discussionsupporting
confidence: 50%
“…Sumoylation of transcription factors and co-factors inhibits transcription in most cases and activates transcription in others (Seeler and Dejean, 2003;Johnson, 2004;Muller et al, 2004). We found that sumoylation of Ets-1 leads to reduced transcription, with the sumoylation defective mutants having a greater capacity to activate transcription than Ets-1.…”
Section: Discussionmentioning
confidence: 74%
“…Our studies show that UV-induced TIP60 sumoylation is correlated with p53 accumulation in the NB, raising the possibility that TIP60-p53 orchestrates the activity in NB. It has been suggested that the NB is involved in chromatin remodeling (Seeler and Dejean, 2003). TIP60, as a HAT, is an important chromatin modifier to regulate chromatin transcription (Kimura and Horikoshi, 1998).…”
Section: Discussionmentioning
confidence: 99%